Immersed tunnels in soft soil conditions experience from the last 20 years. (March 2022) - Olsen, T.; Kasper, T.; de. Wit, J.
Highlights: Immersed tunnel in soft soils has been constructed in Europe since the first in the 1960s. Reliable ground investigations and soil parameters with soil-improvement in mind is important. There are many types of improvement, spanning from replacement, piles to cement deep mixing. Examples are found all around the world, more examples are expected in the future. History show that immersed tunnels can be constructed under very difficult soil conditions. Abstract: Over the last 20 years, large immersed tunnel projects have been planned, designed and constructed under specially challenging ground conditions with soft soils. This has placed extra demands on gaining knowledge about the ground, analysis of settlement behaviour and preparing a design that better controls the level of settlements. Recent improvements in ground engineering technology has allowed immersed tunnels to be constructed in locations that previously would have been regarded as unfeasible, technically unsound or unreasonably costly for immersed tunnel construction. Different types of modern ground investigation methods have been applied, to gain more accurate and reliable ground information. Advanced numerical methods and large-scale statistical data analysis have led to a better representation of the ground conditions and thereby given opportunities for better estimates of tunnel settlement performance. This paper compares the experience gained from recently designed immersed tunnel foundations on soft soils on tunnel projects such as, Busan-Geoje and HZM-link. The paper will highlight similarities identified on different immersed tunnel projects with regards to ground conditions, alignment and chosen foundations, to highlight that it is worth considering immersed tunnel technology for a large sea-crossing (compared to a bridge or bored tunnel), even though ground conditions may be challenging.